Faktor Risiko Kejadian Kecacingan pada Anak Usia Pra Sekolah - Sri Novianty; H. Syahril Pasaribu; Ayodhia Pitaloka Pasaribu (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2018)
Introduction : Intestinal parasite infections are a major health problem in developing countries, especially in children often causing mortality and morbidity.The main cause of intestinal parasite infection is a soil-borne worm called soil-transmitted helminths (STH), the roundworm (Ascaris lumbricoides), the whipworm (Trichuris trichiura) and the hookworm (Ancylostoma duodenale and Necator americanus). Strategy recommended by World Health Organization (WHO) to control it was first focused on school aged children, now preschool-aged children also become one of the high-risk populations of the disease. Therefore it is important to know the risk factors of soil-transmitted helminthiasis in pre-school children.